Antibodies in pemphigus vulgaris. (1st May 2020) - Ivars, M.; España, A.; Alzuguren, P.; Pelacho, B.; Lasarte, J.J.; López‐Zabalza, M.J.
Summary: Pemphigus vulgaris is a blistering skin disorder, which can be severe. Antibodies are a type of protein used by the immune system when fighting off disease or infection, but they can sometimes turn against healthy cells. People with pemphigus vulgaris develop antibodies to various proteins that cement certain skin cells (epidermal cells) together, these include desmoglein 1, desmoglein 3 and desmocollin, together with other unidentified proteins. The damage caused by these antibodies causes separation of epidermal cells, visible under the microscope (and known as acantholysis), eventually resulting in blister formation. The antibodies may act directly on these proteins or indirectly by activation of other inflammatory substances including a d isintegrin a nd m etalloproteinase 10 (ADAM10). The authors, based in Pamplona, northern Spain, aimed to see if blistering induced by different antibodies in patients with pemphigus vulgaris involved activation of ADAM10. They found that antibodies to desmocollin triggered early splitting of the skin, independent of ADAM10. The timing and severity of splitting of skin cells induced by desmoglein antibodies 1 and 3, however, was dependent on the level of antibodies and also on activation of ADAM10. In these, inhibition of ADAM10 prevented acantholysis. The authors propose a role for development of ADAM10 inhibitors in the treatment of the subgroup of patients with pemphigus vulgaris who have antibodies to desmogleins 1 and 3. This is a summary of the study: The involvement of ADAM10 in acantholysis in mucocutaneous pemphigus vulgaris depends on the autoantibody profile of each patient.